Dalālah al-Khafī wa Āliyāt al-Ijtihād: Dirāsah Uṣuliyyah bi Iḥālah Khāṣṣah ilā Qaḍiyah al-Qatl al-Raḥim - Syamsul Anwar (Al-Jami'ah Research Centre, 2003)
This article deals with an uṣūlī concept known among the Hanafi legal theoretician under the name of dalālāt al-khāf (the denotation of an obscure text) and its relation to the mechanism of ijtihād with special reference to the case of euthanasia. The author examines the meaning of the obscure text (al-khāfiy) and discusses the mechanism followed by the uṣūlī in clarifying the ambiguity in it, taking euthanasia as an example. From this, the author concludes that the process of legal reasoning in founding out a legal rule for a case involves three poles which have dialectical relations to one another: the text, the reality, and the objective of law. The text with its symbolic characteristic and its relying upon generalization and abstraction in expressing an object enables the mujtahid to add a new meaning to it and this meaning is produced through an adequate understanding of the case and the spatio-temporal space in which it happens in the one hand and through considering the objective of law as meaning space on the other hand. The reality of the case shades light in our understanding of the text, while the text in the same time gives us a clear orientation in coping with the reality.